2012
DOI: 10.1186/1471-2458-12-53
|View full text |Cite
|
Sign up to set email alerts
|

Migrant health in French Guiana: Are undocumented immigrants more vulnerable?

Abstract: BackgroundFew data exist on the health status of the immigrant population in French Guiana. The main objective of this article was to identify differences in its health status in relation to that of the native-born population.MethodsA representative, population-based, cross-sectional survey was conducted in 2009 among 1027 adults living in Cayenne and St-Laurent du Maroni. Health status was assessed in terms of self-perceived health, chronic diseases and functional limitations. The migration variables were imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 39 publications
4
49
1
5
Order By: Relevance
“…In addition the characteristics of the MS-MV identified in this analysis, including young age, low socio-economic status and poor health are compatible with previous research describing undocumented immigrants. International evidence has suggested that those that do not report their migration status may be commonly undocumented immigrants [11,28,29] and under-estimation of immigrants in national representative surveys has been frequently reported in the past [1,3,30,31,48]. It is also notable that when the immigrants and the missing values are added together, they account for 1.63% of the total Chilean population, which is very similar to the prevalence of immigrants in the Chilean population recently reported by the Chilean government (1.6-1.8%) [15,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition the characteristics of the MS-MV identified in this analysis, including young age, low socio-economic status and poor health are compatible with previous research describing undocumented immigrants. International evidence has suggested that those that do not report their migration status may be commonly undocumented immigrants [11,28,29] and under-estimation of immigrants in national representative surveys has been frequently reported in the past [1,3,30,31,48]. It is also notable that when the immigrants and the missing values are added together, they account for 1.63% of the total Chilean population, which is very similar to the prevalence of immigrants in the Chilean population recently reported by the Chilean government (1.6-1.8%) [15,35].…”
Section: Discussionmentioning
confidence: 99%
“…They also report lack of access and limited use of health care [9]. Relatively little is known however about undocumented migrants worldwide [10,11], including those in the Latin American region [12-14]. Further research regarding migrants is urgently required to improve the living conditions and health of these populations, and especially those living in socioeconomic vulnerability, such as undocumented immigrants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of health and migration has up to now been examined primarily within the context of special topics such as the vulnerability of undocumented migrants (Jolivet et al. ), the health of migrant children (Hjern and Bouvier ), migrant women in reproductive age (Iglesias et al. ), elderly migrants (Reijneveld, Westhoff, and Hopman‐Rock ), depression and generalized anxiety of migrant groups in comparison with the native population (Levecque, Lodewyckx, and Vranken ), stress and mental ill health of migrants (Tinghög ), or migrants in retirement age (Pudaric, Sundquist, and Johansson ).…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors have questioned the existence of healthy migrant effects and conflicting results have been found in some studies 8,18 . Much less has been studied regarding the healthy migrant effect within Latin America 8,19 , despite the growing intra-regional mobility of people in this region 20 . This study describes the first large-scale quantitative analysis of the health of immigrants to Chile, most of them from other Latin American countries.…”
mentioning
confidence: 99%